Shearing strength as an additional selection criterion for quality in Brachiaria ecotypes - Hughes, N.R.G.; Valle, Cacilda Borges do; Sabatel, V.; Boock, J.; Jessop, N.S.; Herrero, Mario (Cambridge University Press, 2000)
Leaves of 12 accessions of Brachiaria sp. (three accessions from each of four species) were subjected to tests of shearing strength using a Warner Bratzler meat shear. Morphological measurements of these leaves were also taken in an attempt to standardize shearing strength measurements per unit of leaf tissue. The technique was evaluated for its capacity to detect differences between accessions of the same species. All samples were also analysed for dry matter (DM), organic matter (OM), neutral detergent fibre (NDF), acid detergent fibre (ADF), lignin, crude protein, silica and digestibility in order to relate measures of physical strength to chemical components. Results demonstrated the presence of a clear relationship between shearing strength and structural (cell wall) components. Correlations between shearing strength and NDF, ADF and lignin were 0·74, 0·82 and 0·80 respectively. The technique identified clear differences between accessions of the same species (P < 0·05). These measurements can thus be used as a powerful tool for identifying forage plants of superior nutritional quality within selection programmes. Measurements of strength standardized for morphological characteristics illustrated that the ranking of the samples varied considerably depending on which morphological character was used.